Impact of soil erosion potential uncertainties on numerical simulations of the environmental fate of radiocesium in the Abukuma River basin. (December 2020) - Ikenoue, Tsubasa; Shimadera, Hikari; Kondo, Akira
Abstract: The Fukushima Dai-ichi Nuclear Power Plant accident in March 2011 resulted in the deposition of significant quantities of radionuclides, including radiocesium ( 137 Cs), over a wide area. Most of the deposited 137 Cs is strongly adsorbed on fine soil particles such as clay and silt near the ground surface. Therefore, to estimate the environmental fate of 137 Cs, it is necessary to predict its transport with eroded sediment in rainfall-runoff processes. In this study, a distributed radiocesium prediction model was applied to simulations of 137 Cs transport associated with hydrological processes in the Abukuma River Basin, the largest river system in Fukushima, over the period of 2011–2012. The soil erosion potential, which is a key input to the distributed radiocesium prediction model, was estimated using the Universal Soil Loss Equation (USLE). This study focused on the uncertainty in estimating the environmental fate of 137 Cs associated with the USLE factors. The USLE has five physically meaningful factors: the rainfall and runoff factor ( R ), soil erodibility factor ( K ), topographic factor ( L S ), cover and management factor ( C ), and support practice factor ( P ). Because the USLE factors were determined using various methods, R, L S, and the product of C and P ( C × P ) were divided into two, three, and five cases, respectively, based on previous studies. Therefore, we conducted 30 different simulations. The average total 137 Cs outflow during the computational period in the simulation cases using the same USLE factors was 13.3 and 11.7 TBq for R (two cases), 12.6, 13.9 and 10.9 TBq for L S (three cases), and 26.5, 8.64, 0.47, 22.8 and 4.03 TBq for C × P (five cases). For the total outflow, C and P had the highest uncertainty of all the USLE factors. The outflow rates of the average total 137 Cs in the simulation cases using the same C and P from the croplands and forest areas and from the undisturbed croplands and paddy fields were 62–91% and 18–34%, respectively. These results were due to the high erodibility of the croplands, the large forest areas in grids with high 137 Cs deposition density, and the high concentration of 137 Cs in the soil of the undisturbed croplands and paddy fields. This study indicates that land use, especially forest areas, croplands, and undisturbed paddy fields, has a significant impact on the environmental fate of 137 Cs. Highlights: A distributed radiocesium prediction model was used to simulate the environmental fate of 137 Cs in the Abukuma River Basin. We evaluated impact of soil erosion potential uncertainties on the environmental fate of 137 Cs. Land use, especially forest areas, croplands, and undisturbed paddy fields, had a significant impact on the 137 Cs outflow.